Global, regional, and national burden of cardiomyopathy (including alcoholic cardiomyopathy and others) from 1990 to 2021: An analysis of data from the global burden of disease study 2021 and forecast to 2040 - Haoyang Chen; Ruifeng Liang; Yanzhang Tian (PLoS ONE, 2026)
Background Cardiomyopathy is a disease that can lead to severe cardiac symptoms and has seen an increasing number of cases in recent years. This study aims to analyze the incidence, mortality, and disability-adjusted life years of cardiomyopathy (including alcoholic cardiomyopathy and other cardiomyopathy) globally, as well as in different regions and countries, from 1990 to 2021, at different gender, age, and socio-demographic index levels. Methods All data relevant to the burden of disease analysis in this study were obtained from the 2021 Global Burden of Diseases, Injuries, and Risk Factors Study (GBD), encompassing alcoholic cardiomyopathy (AC) and other cardiomyopathy (OC). The overall burden of total cardiomyopathy (TC) was evaluated by integrating data about AC and OC, with 95% confidence intervals calculated based on the 95% uncertainty interval (UI) width divided by the standardized error value, determined by 1.96 × 2. Temporal patterns and trends in age-standardized prevalence rates (ASPR), mortality rates (ASDR), and disability-adjusted life years (ASR_DALYs) for global TC, as well as for AC and OC burden calculations, their estimated annual percentage changes (EAPCs) were calculated, assessed, and visualized. The analysis was categorized by gender, 20 age groups, 21 GBD regions, 204 countries/regions, and 5 socio-demographic index (SDI) regions. The burden of disease prediction model was subjected to Bayesian age-period-cohort (BAPC) modeling to derive predictions for the period from 2022 to 2040. All statistical analyses and mappings were conducted using the R statistical package version 4.4.3. Results In 2021, the global burden of TC remains considerable, with a total of 4752361.3, including AC: 528429 and OC: 4223932.2; the ASPRs (per 100,000 persons) were 59.5, 6.2 and 53.3; the ASDR (per 100,000 persons) were 4.5, 0.7 and 3.7; the age-standardized DALYs were 129.8, 25.3 and 104.5. In the aspect of AC, a considerable disparity in age-standardized prevalence, mortality, and DALYs was observed between the regional, national, and gender levels. The predictive results indicated that from 2021 to 2040, the ASPR of TC and OC showed a general increasing trend, while that of AC showed a decreasing trend. The ASDR and ASR_DALYs of TC, OC, and AC showed a general decreasing trend. Conclusions Globally, there has been an observed increase in the ASPR of TC and OC, while AC presented a decreasing trend, with significant regional, age, and gender variations in future trends. Although future projections in this study suggested a decline in ASDR and ASR_DALYs of TC, AC, and OC, there is a need to continue controlling the burden of disease in TC, AC, and OC studies to respond to the corresponding epidemiological trends and reduce the burden of them to some extent.